Gone, but not Forgotten - Barbara Pisani (Radcliffe Medical Media, 2020)
The global health and economic impact of the coronavirus disease 2019 (COVID-19) pandemic has rocked our communities and way of life. With millions infected around the globe, and hundreds of thousands of lives lost, there has been a paradigm shift in how clinicians evaluate and care for patients in multiple different types of healthcare settings. Many patients are reluctant to seek medical attention for cardiovascular illnesses, and late presentations of acute cardiac issues are raising the morbidity and mortality for treatable cardiac conditions. In this expert opinion, the authors canvas the many challenges in the diagnosis, treatment and delivery of care to patients with congestive heart failure and acute coronary syndromes during the COVID-19 pandemic.